Synergistic fermentation of vitamin B2 (riboflavin) bio-enriched soy milk: optimization and techno-functional characterization of next generation functional vegan foods - Ananya Rana; Neetu Kumra Taneja; Anupama Singh; Tejpal Dhewa; Vikram Kumar; Ankur Kumar; Komal Chauhan; Vijay Juneja; Harinder Singh Oberoi (Discover Food)
Abstract Vitamin B2 (riboflavin) is essential for cellular growth, energy production, and redox potential. Certain lactic acid bacteria (LAB) can synthesize B2 in low levels in fermented products, however it is mostly retained inside the cell. This study aimed to develop B2-enriched soymilk by fermenting with B2-producing probiotic Lactiplantibacillus plantarum strains and traditional starter culture Lactobacillus acidophilus NCIM2902. Using the central composite design approach, processing parameters were optimized for enhanced B2 content and probiotic count. Six independent variables were assessed: temperature (A: 35–45 °C), pH (B: 4–6), time (C: 3–18 h), and inoculum size for strains L. plantarum MTCC 25432 (D: 1–2%), L. plantarum MTCC 25433 (E: 1–2%), and L. acidophilus NCIM 2902 (F: 1–2%). The second-order model effectively predicted responses, identifying optimal fermentation conditions for developing vitamin B2-enriched soymilk: temperature (A) 36 °C, pH (B) 5.5, fermentation time (C): 11 h, inoculum size for L. plantarum MTCC 25432 (D): 2%, MTCC 25433 (E): 2%, and L acidophilus NCIM (F): 0.43%. These conditions resulted in a threefold increase in B2 concentration (481 µg/L) while maintaining a probiotic count of 9 logs CFU/mL. Additionally, techno-functional characterization, including rheology and texture profile analysis, showed that enhanced protease activity of co-cultured LAB improved protein hydrolysis (6259 nm), positively impacting the water holding capacity (WHC) and overall acceptability of the fermented soymilk. This optimized fermentation process represents a novel approach to developing nutritionally enhanced dairy-free soy products with high riboflavin content, utilizing the synergistic benefits of co-fermentation by two riboflavin-producing L. plantarum strains and traditional starter culture of L. acidophilus. This advancement is particularly significant for lactose-intolerant and vegan consumers who may lack sufficient dietary sources of Vitamin B2.